Histerectomía en pacientes atendidas en el Área de Ginecología y Obstetricia del Hospital General Isidro Ayora de Loja. - Arizaga Paredes, Viviana del Pilar (2017)
Hysterectomy has become one of the most widely used surgical procedures worldwide for the treatment of benign and malignant uterine pathologies, reducing morbidity and mortality. The present research work named Hysterectomy in patients attended in the gynecology and obstetrics area in the Isidro Ayora General Hospital of Loja, type of retrospective, cross-sectional descriptive, correlational study. The general objective is to determine the hysterectomy in patients attended in the Gynecology and Obstetrics Area in the Isidro Ayora general hospital of Loja. The specific objectives are to know the frequency of hysterectomy according to the age group, to identify the preoperative diagnosis and to compare the main complications according to the type and surgical approach of hysterectomy used in the patients attended in the Gynecology and Obstetrics Area in the Isidro Ayora general hospital of Loja period 2015. The sample was 48 patients, obtaining the following results: the age group in which it was performed with greater frequency hysterectomy is 36 to 45 years and 46 to 55 years corresponding to 35.42% and 33.33% respectively. The preoperative diagnosis that predominated is uterine myomatosis with 66.67%, the complications correspond according to the surgical approach to 8.3% hemorrhage by simple abdominal hysterectomy, same as the corresponding type to subtotal hysterectomy in 12% and total 9%; followed by 4.2% to bladder injury due to simple abdominal hysterectomy, and 9% to type of total hysterectomy. Keywords: Hysterectomy, complications, type of surgery approach.